Characteristics of steroid hormones in systemic lupus erythematosus revealed by GC/MS-based metabolic profiling - Wu, Dehong; Ye, Lingxia; Zhang, Xiafeng; Yin, Mengdi; Guo, Yixuan; Zhou, Jia (Frontiers in Endocrinology, 2023)
Systemic lupus erythematosus (SLE) is a systemic autoimmune disease with a remarkable predominance in female, suggesting that steroid hormones may be involved in the pathogenesis. Herein, more than 70 kinds of steroids in urine were detected by gas chromatography/mass spectrometry (GC/MS) to reveal SLE-specific steroid alterations. Principle component analysis demonstrated that the steroid profile was obviously distinguished between SLE patients and controls. Lower level of total androgens was observed in patients, and 9 androgens (DHEA, testosterone, Etio, androsterone, βαβ-Diol, Epi-An, Epi-DHT, 16α-OH-DHEA, A-Diol) underwent significant decrease. Besides, SLE patients exhibited slightly higher level of total estrogens than controls, and 3 estrogens (17-Epi-E3, 17α-E2, E3) were remarkably increased. Furthermore, we identified the elevation of 2 sterols (Lan, Chol), and the reduction of 1 corticoid (11-DeoxyF) and 2 progestins (5α-DHP, 11β-OH-Prog) in patients. In this study, metabolic signature of urinary steroids associated with SLE was comprehensively defined by GC/MS for the first time, and steroid metabolism disorders were found in SLE patients, especially the conversion of androgens to estrogens. Our findings will provide new insights for a deeper understanding of the mechanism of steroid hormones in the pathogenesis of SLE, and help to unravel the reason of sexual disparity in SLE.